The Meal that reconnects : eucharistic eating and global food crisis - McGann, Mary E. (Collegeville, Minnesota : Liturgical Press, 2020)
"Discusses the sacredness of eating, the planetary interdependence that the sharing of food entails, and the destructiveness of the industrial food system, presenting the food crisis as a spiritual crisis. The author invites communities to reclaim the foundational meal character of eucharistic celebration while offering pertinent strategies for this renewal"-- provided by publisher
pt. 3 Eucharist: the meal that reconnects
Includes bibliographical references and index.
Keywords: Dinners and dining -- Religious aspects -- Catholic Church; Lord's Supper -- Catholic Church; Hunger -- Religious aspects -- Catholic Church; Food Supply -- Moral and ethical aspects; Food supply -- Religious aspects -- Catholic Church